Collegiate women's wrestling body fat percentage and minimum wrestling weight values: time for revisiting minimal body fat percent? - Andrew R. Jagim; Grant M. Tinsley; Robert A. Oppliger; Craig A. Horswill; Ward C. Dobbs; Jennifer B. Fields; Cliff Cushard; Paul D. Rademacher; Margaret T. Jones (Taylor & Francis Group, 2024)
ABSTRACTBackground The estimation of body fat percentage (BF%) in wrestling is used to determine the minimum wrestling weight (MWW) and lowest allowable weight class (MWC) in which wrestlers are eligible to compete. A 12% minimum threshold is currently used for women wrestlers, yet a potential increase for safety has been discussed. Because of the novelty of collegiate women's wrestling, there is a paucity of literature available on the body composition norms of this population. The purpose of this study was to provide a descriptive summary of BF% and MWW values of female wrestlers and how MWW values would change with the use of different BF% thresholds.Methods Data from the 2022-2023 collegiate season were retrospectively analyzed resulting in a sample of 1,683 collegiate women wrestlers from the National Association of Intercollegiate Athletics (NAIA, n = 868) and the National Collegiate Athletics Association (NCAA, n = 815). All wrestlers completed skinfold assessments for weight certification at the start of the competition season. The skinfold values were used to estimate BF% using the Slaughter skinfold prediction equation. Frequency statistics and descriptive analysis were performed to compute normative MWW and BF% profiles. BF% thresholds of 12% (12MWW) and the BF% value defined as the lowest 5th percentile, which would be considered unusually lean, were used to determine the resulting MWW and MWC for each method. The lowest recorded weight and weight class division throughout the season was also recorded for each wrestler.Results There was a positively skewed (0.94) and platykurtic (1.86) distribution of MWW values. The median ± interquartile range BF% for all wrestlers was 27.4 ± 10.22%, with 17% BF representing the 5th percentile. Only 354 out of 1,579 (22.4%) wrestlers competed in their lowest allowable weight class, based on the 12MWW. Of these 354 wrestlers, the mean BF% was 21.3 ± 5.2% at weight certification with only n = 17 being at or below 12% body fat and an average weight loss of 11.1 ± 8.8 lbs. from the time of weight certification. Throughout the season, wrestlers competed at weights that were, on average (mean ± SD), 19.4 ± 16.9 lbs. higher than their 12MWW (95% CI: 18.6, 20.2 lbs. p < 0.001; effect size [ES] = 1.1), 13.4 ± 19.0 lbs. higher than the 17MWW (p < 0.001; ES = 0.70), and 8.7 ± 8.3 lbs. lower than their weight at the certification (95% CI: 8.3, 9.1 lbs. p < 0.001; ES = 1.1).Conclusions Nearly all BF% values were well above the 12% threshold used to determine MWW. Increasing the minimum BF% threshold from 12% to 17% would affect a small percentage of wrestlers, likely reduce the need for excessive weight cutting, and minimize the deleterious health effects of an athlete at such a low BF%.